A secondary battery and unmanned aerial vehicle using the same

By using antimony carbon composite material and amorphous carbon material to form a three-dimensional network structure in the negative electrode active material layer of the secondary battery, the problem of insufficient energy density of secondary batteries in the prior art is solved, and the endurance of the drone is improved.

CN118136919BActive Publication Date: 2024-12-13AIDENGDA NEW ENERGY BATTERY MATERIAL TECHNOLOGY (GUANGZHOU) CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202410174140.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-07
Publication Date
2024-12-13
Estimated Expiration
2044-02-07

AI Technical Summary

Technical Problem

The volume energy density of existing secondary batteries is difficult to meet the battery life requirements under special sizes, and it is impossible to effectively improve the range of the drone.

Method used

The antimony carbon composite material and amorphous carbon material are used to form a three-dimensional network structure in the negative electrode active material layer, which improves the structural strength and storage activity of the electrode material, enhances the rate performance and energy density, and suppresses the expansion of metal antimony through the carbon cladding layer. Improve deformation of the internal structure of the electrode.

Benefits of technology

The structural stability and high energy density of the negative electrode material are achieved, the circulation and rate performance of the secondary battery are improved, and commercial applications that meet high battery life requirements are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118136919B_ABST
    Figure CN118136919B_ABST
Patent Text Reader

Abstract

The present invention provides a secondary battery and a drone using the same, the secondary battery comprising a positive electrode sheet and a negative electrode sheet, the negative electrode sheet is provided with a negative electrode active material layer, the negative electrode active material layer contains an antimony carbon composite material and an amorphous carbon material; the amorphous carbon material is a mesoporous material, and the pore diameter of the amorphous carbon material is 20-30nm; in the antimony carbon composite material, the antimony element content is 1%-50% calculated by mass percentage. The negative electrode active material layer provided by the present invention forms a three-dimensional network structure in situ by introducing the antimony carbon composite material and the amorphous carbon material, which can not only improve the structural strength of the electrode material, but also improve its performance of storing active materials, so as to have good cycle performance, rate performance and high energy density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of secondary batteries, and in particular relates to a secondary battery and a drone using the secondary battery. Background Art

[0002] With the progress of society and the continuous development of various technologies, compared with traditional aircraft, drones have better control performance, lower space and maintenance costs for take-off and landing, and are smaller in size, easy to hide, and not easily discovered. Therefore, they have received more attention and invested more in development in both the military and civilian fields. After a long period of development and the continuous improvement of modern electronic technology, drone technology has become more mature, the types of drones have become more diversified, the application scenarios of drones have become wider, and the market size has continued to grow rapidly. According to statistics, there will be more than 12,000 drone companies in China in 2021, with a total industry output value of 87 billion yuan. The low-altitude economy represented by drones is expected to become a new engine to promote social and economic growth. The drone battery series that provides power for drones has also seen strong growth.

[0003] With the widespread use of drones, the technical requirements for drones are getting higher and higher. Safe power sources and stable endurance have become the main problems that drones need to solve at this stage. At present, most drones on the market use secondary batteries as the power source for flight and flight control. The manufacturing cost of secondary batteries is relatively lower. Due to the unique properties of their materials, secondary batteries with moderate size and low quality can be manufactured. Batteries can store more energy in a smaller space and have the significant advantage of stable output. However, because the weight and volume of secondary batteries are proportional to the capacity, but inversely proportional to the range, the energy density of secondary batteries needs to be improved so that they can meet the current market requirements for the range of drones and enable drones to fly farther.

[0004] The Chinese patent application number 2023111410884 discloses a method for improving the structural stability of a secondary battery using an antimony-based negative electrode active material during cyclic charge and discharge. However, the volume energy density of the negative electrode active material is difficult to meet the endurance requirements under special sizes. Therefore, it is urgent to develop a secondary battery that can meet the endurance requirements under special sizes. Summary of the invention

[0005] In order to improve the volume energy density of a secondary battery, the present invention provides a secondary battery and a drone using the same.

[0006] According to one aspect of the present invention, a secondary battery is provided, which includes a positive electrode plate and a negative electrode plate. The negative electrode plate is provided with a negative electrode active material layer, and the negative electrode active material layer contains an antimony carbon composite material and an amorphous carbon material; the amorphous carbon material is a mesoporous material, and the pore diameter of the amorphous carbon material is 20 to 30 nm; in the antimony carbon composite material, the antimony element content is 1% to 50% calculated by mass percentage.

[0007] The negative electrode active material layer provided by the present invention forms a three-dimensional network structure in situ by introducing antimony-carbon composite materials and amorphous carbon materials, which can not only improve the structural strength of the electrode material, but also improve its performance of storing active materials, thereby having excellent rate performance and high energy density. On the one hand, the three-dimensional network structure formed ensures the structural stability of the negative electrode active material layer, so that the negative electrode material has a higher consistency when the volume changes, that is, the changes in the three-dimensional network conductive structure when lithium ions or sodium ions are extracted have a higher consistency. As a result, the phenomenon of cracks inside the negative electrode caused by the non-three-dimensional structure of the traditional binder and the negative electrode material can be reduced, thereby improving the problem of deformation or even collapse of the internal structure of the electrode. On the other hand, the three-dimensional network structure formed can also provide expansion space for inserting lithium ions and sodium ions, so that it can expand to easily accommodate lithium ions and sodium ions, thereby increasing the capacity of the negative electrode material. Therefore, the negative electrode active material provided by the present invention is based on the three-dimensional network structure formed in situ by antimony-carbon composite materials and amorphous carbon materials, and has good cycle performance, rate performance, and high capacity and energy density.

[0008] Preferably, the specific surface area of ​​the amorphous carbon material is 700 to 900 g / m 2 .

[0009] Preferably, the oil absorption value of the amorphous carbon material is 30-600 mL / 100 g. The oil absorption value is related to the structure of the amorphous carbon material and will affect the lithium ion transmission speed of the prepared negative electrode sheet.

[0010] Preferably, the antimony-carbon composite material comprises a metal antimony core and a carbon coating layer. In the antimony-carbon composite material, the metal ladder has a higher capacity and a higher discharge voltage; and the carbon coating layer can reduce the interface side reaction between the metal ladder and the electrolyte and inhibit the expansion of the metal antimony. Therefore, the antimony-carbon composite material has good cycle stability and structural stability.

[0011] Preferably, the antimony-carbon composite material satisfies: in the Raman spectrum of the antimony-carbon composite material, the peak intensity I of the D peak is D The peak intensity of the G peak is G Ratio I D / I G=0.5~1.6; In the X-ray diffraction spectrum of the antimony-carbon composite material, the peak intensity C of the characteristic peak of the (110) surface 110 The peak intensity C of the characteristic peak of (002) surface 002 Ratio C 110 / C 002 =0.043~0.085.

[0012] Preferably, the particle size distribution of the antimony-carbon composite material satisfies D 50 =2.5~5μm, the particle size distribution of amorphous carbon materials meets D 50 = 0.55 to 0.65 μm. When both the antimony-carbon composite material and the amorphous carbon material meet this particle size range, the two can be evenly distributed, thereby enhancing the stability and electrochemical performance of the formed three-dimensional network structure, thereby improving the rate performance of the secondary battery.

[0013] Preferably, D of the antimony-carbon composite material 90 =8~10μm, D of antimony carbon composite material 10 =0.5~1.5μm.

[0014] Preferably, D of the amorphous carbon material 90 = 0.8~1.56μm, D of amorphous carbon materials 10 =0.25~0.35μm.

[0015] Preferably, the specific surface area of ​​the antimony-carbon composite material is 1.5 to 4.5 m 2 / g.

[0016] Preferably, in the negative electrode active material, the mass ratio of antimony-carbon composite material to amorphous carbon material is 8 to 10:1.

[0017] Preferably, the antimony-carbon composite material and the amorphous carbon material are mixed for 0.5 to 7 hours to obtain the negative electrode active material.

[0018] Preferably, the compaction density of the negative electrode active material layer is 1.5 to 1.7 g / m 2 .

[0019] Preferably, the thickness of the negative electrode plate is 70-90 μm.

[0020] Preferably, a positive electrode active material layer is provided on the positive electrode plate, and the positive electrode active material contained in the positive electrode active material layer includes at least one of nickel-cobalt-manganese ternary material, lithium iron phosphate material, lithium iron manganese phosphate material, lithium cobalt oxide material, and lithium-rich manganese-based material.

[0021] A second aspect of the present invention provides an unmanned aerial vehicle, the unmanned aerial vehicle includes a battery system, and the battery system includes the secondary battery as described above. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The rate performance of the secondary batteries prepared in Comparative Example 1 and Example 1. DETAILED DESCRIPTION

[0023] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention and the drawings in the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0024] Example 1

[0025] The raw materials used in this embodiment include: antimony source, antimony trioxide, spherical, D 50 =100nm; dispersant, polyvinyl pyrrolidone; organic carbon source, glucose; graphite, flake, D 50 =5μm; amorphous carbon material, mesoporous material, pore diameter is 25nm, D 50 =0.6μm, specific surface area is 800g / m 2 ; Solvent, water.

[0026] The above raw materials are used to prepare antimony carbon composite materials and negative electrode active materials according to the following operations:

[0027] S1. Weigh the raw materials according to the mass ratio of antimony trioxide: polyvinyl pyrrolidone: glucose: graphite: solvent water = 1:1:6:1:100, mix the weighed raw materials, and use ultrasonic dispersion for 60 minutes, during which high-speed stirring is provided at a stirring speed of 150 r / min to obtain a uniform reaction slurry;

[0028] S2. The reaction slurry obtained in S1 was stirred under heating conditions until the solvent was completely volatilized, the stirring speed was 150 r / min, the heating temperature was 50 ° C, and then the remaining material was dried at 50 ° C, and then the remaining dry material was ground to obtain a precursor;

[0029] S3. The precursor prepared in S2 is placed in a muffle furnace with a reducing gas, wherein the reducing gas is an argon-hydrogen mixture gas, in which the volume content of hydrogen is 5%, and then the muffle furnace is heated to 650°C at a heating rate of 2°C / min and kept warm for 2h. During this process, antimony trioxide is converted into metallic antimony, and glucose undergoes a pyrolysis reaction to form a carbon coating layer on the surface of the metallic antimony. After the reaction is completed, an antimony-carbon composite material (D 50 =3.6μm, I D / IG =1.12, C 110 / C 002 =0.053);

[0030] S4. The obtained antimony-carbon composite material was then mixed with an amorphous carbon material (with a void diameter of 25 nm) and ground for 30 minutes to obtain a negative electrode active material, wherein, according to the mass ratio, the antimony-carbon composite material: the amorphous carbon material = 9:1, and the I of the antimony-carbon composite material D / I G =1.10, C 110 / C 002 =0.054.

[0031] Subsequently, the prepared negative electrode active material and binder (LA133) were mixed at room temperature in a mass ratio of 9.25:0.75, and then water was added for further mixing to obtain electrode slurry. After the electrode slurry was coated on the copper foil using a scraper, the copper foil coated with the electrode slurry was placed in an oven for vacuum drying at 80°C for 12 hours. Next, the vacuum-dried copper foil was punched into a circular electrode sheet with a diameter of 12 mm and a thickness of 80 μm using a punching machine.

[0032] Example 2

[0033] The types of raw materials used in this embodiment for preparing the negative electrode active material and the pole piece are the same as those in Example 1. The above raw materials are used, and the method for preparing the negative electrode active material provided in Example 1 is referred to, to prepare the negative electrode active material of this embodiment. The difference from Example 1 is that in terms of the raw material ratio, calculated by mass ratio, the antimony carbon composite material: amorphous carbon material = 8:1. Except for the above differences, all process steps for preparing the negative electrode active material and the pole piece of this embodiment are strictly consistent with those of Example 1.

[0034] Example 3

[0035] The types of raw materials used in this embodiment for preparing the negative electrode active material and the pole piece are the same as those in Example 1. The above raw materials are used, and the method for preparing the negative electrode active material provided in Example 1 is referred to, to prepare the negative electrode active material of this embodiment. The difference from Example 1 is that in terms of the raw material ratio, calculated by mass ratio, the antimony carbon composite material: amorphous carbon material = 10:1. Except for the above differences, all process steps for preparing the negative electrode active material and the pole piece of this embodiment are strictly consistent with those of Example 1.

[0036] Example 4

[0037] The raw materials used in this embodiment to prepare the negative electrode active material and the pole piece are the same as those in Example 1. The negative electrode active material and the pole piece of this embodiment are prepared by using the above raw materials and referring to the method for preparing the negative electrode active material and the pole piece provided in Example 1. The difference from Example 1 is that when preparing the pole piece in this embodiment, the antimony carbon composite material used is I D / I G =0.36, C 110 / C 002 =0.045. In this embodiment, the insulation temperature of the muffle furnace is adjusted to 1100° C. in S3 for preparing the antimony-carbon composite material to achieve the above difference. In addition to the above difference, all process steps for preparing the negative electrode active material and the electrode sheet in this embodiment are strictly consistent with those in Example 1.

[0038] Example 5

[0039] The raw materials used in this embodiment to prepare the negative electrode active material and the pole piece are the same as those in Example 1. The negative electrode active material and the pole piece of this embodiment are prepared by using the above raw materials and referring to the method for preparing the negative electrode active material and the pole piece provided in Example 1. The difference from Example 1 is that when preparing the pole piece in this embodiment, the antimony carbon composite material used is I D / I G =0.56, C 110 / C 002 =0.036. In this embodiment, the insulation temperature of the muffle furnace is adjusted to 400° C. in S3 for preparing the antimony-carbon composite material to achieve the above difference. In addition to the above difference, all process steps for preparing the negative electrode active material and the electrode sheet in this embodiment are strictly consistent with those in Example 1.

[0040] Example 6

[0041] The raw materials used in this embodiment to prepare the negative electrode active material and the pole piece are the same as those in Example 1. The negative electrode active material and the pole piece of this embodiment are prepared by using the above raw materials and referring to the method for preparing the negative electrode active material and the pole piece provided in Example 1. The difference from Example 1 is that when preparing the pole piece in this embodiment, the antimony carbon composite material D 50 = 2 μm, D of amorphous carbon materials 50 =0.7 μm. Except for the above differences, all process steps for preparing the negative electrode active material and the electrode sheet in this embodiment are strictly consistent with those in Embodiment 1.

[0042] Example 7

[0043] The raw materials used in this embodiment to prepare the negative electrode active material and the pole piece are the same as those in Example 1. The negative electrode active material and the pole piece of this embodiment are prepared by using the above raw materials and referring to the method for preparing the negative electrode active material and the pole piece provided in Example 1. The difference from Example 1 is that when preparing the pole piece in this embodiment, the antimony carbon composite material D 50 =6.32μm, D of amorphous carbon material 50 =0.4 μm. Except for the above differences, all process steps for preparing the negative electrode active material and the electrode sheet in this embodiment are strictly consistent with those in Embodiment 1.

[0044] Example 8

[0045] The raw materials used in this embodiment to prepare the negative electrode active material are the same as those in Example 1. The above raw materials are used, and the method for preparing the negative electrode active material and the pole piece is provided with reference to Example 1 to prepare the negative electrode active material and the pole piece of this embodiment. The difference from Example 1 is that the method for preparing the antimony-carbon composite material in this embodiment is to directly calcine after mixing antimony trioxide and carbon material to obtain an antimony-carbon composite material doped with carbon. In addition to the above differences, the raw materials and process steps used in this embodiment are strictly consistent with those in Example 1. Specifically, the method for preparing the antimony-carbon composite material in this embodiment is:

[0046] The raw materials are weighed according to the mass ratio of antimony trioxide: polyvinyl pyrrolidone: glucose: graphite = 1:1:6:1, the weighed raw materials are mixed, and then the mixed solid is placed in a muffle furnace with a reducing gas after ball milling, wherein the reducing gas is an argon-hydrogen mixture, and the volume content of hydrogen in the argon-hydrogen mixture is 5%, and then the muffle furnace is heated to 600°C at a heating rate of 2°C / min and kept warm for 2h to obtain an antimony-carbon composite material.

[0047] Comparative Example 1

[0048] The material used to prepare the pole piece in this comparative example is graphite. The above raw materials are used, and the method for preparing the pole piece provided in Example 1 is referred to, to prepare the pole piece of this comparative example. Except for the above differences, the process steps used in this comparative example are strictly consistent with those in Example 1.

[0049] Comparative Example 2

[0050] This comparative example is used to prepare the raw materials containing negative electrode active materials, and the antimony carbon composite material is replaced by graphite in equal parts by mass. The other raw material types are the same as those in Example 1. The above raw materials are used, and the method for preparing negative electrode active materials and pole pieces is provided in reference to Example 1 to prepare the negative electrode active materials and pole pieces of this comparative example. The difference from Example 1 is that this comparative example replaces the antimony carbon composite material with graphite in equal parts by mass to prepare the negative electrode active material. In addition to the above differences, the raw materials and process steps used in this comparative example are strictly consistent with those in Example 1.

[0051] Comparative Example 3

[0052] The raw materials used in this comparative example to prepare the negative electrode active material do not include amorphous carbon materials, and the remaining raw materials are the same as those in Example 1. The above raw materials are used, and the method for preparing the negative electrode active material and the pole piece is provided with reference to Example 1 to prepare the negative electrode active material and the pole piece of this comparative example. The difference from Example 1 is that this comparative example omits the step of adding the amorphous carbon material to prepare the negative electrode active material. In addition to the above differences, the raw materials and process steps used in this comparative example are strictly consistent with those in Example 1.

[0053] Comparative Example 4

[0054] This comparative example is used to prepare raw materials containing negative electrode active materials, in which equal parts by mass of microporous materials are substituted for mesoporous materials, and the remaining types of raw materials are the same as those in Example 1, wherein the pore diameter of the microporous material is 1.25±0.75 nm. Using the above raw materials, referring to the method for preparing negative electrode active materials and pole pieces provided in Example 1, the negative electrode active materials and pole pieces of this comparative example are prepared. The difference from Example 1 is that this comparative example prepares negative electrode active materials with equal parts by mass of microporous materials instead of mesoporous materials. Except for the above differences, the raw materials and process steps used in this comparative example are strictly consistent with those in Example 1.

[0055] Comparative Example 5

[0056] The raw materials used in this comparative example to prepare the negative electrode active material are the same as those in Example 1. The above raw materials are used, and the method for preparing the negative electrode active material and the pole piece provided in Example 1 is referred to, to prepare the negative electrode active material and the pole piece of this comparative example. The difference from Example 1 is that the antimony content of the antimony-carbon composite material used in this comparative example is 55%. In addition to the above differences, the raw materials and process steps used in this comparative example are strictly consistent with those in Example 1.

[0057] Comparative Example 6

[0058] The raw materials used in this comparative example to prepare the negative electrode active material are the same as those in Example 1. The above raw materials are used, and the method for preparing the negative electrode active material and the pole piece provided in Example 1 is referred to, to prepare the negative electrode active material and the pole piece of this comparative example. The difference from Example 1 is that the pore diameter of the amorphous carbon material used in this comparative example when preparing the negative electrode active material is 10nm. In addition to the above differences, the raw materials and process steps used in this comparative example are strictly consistent with those in Example 1.

[0059] Comparative Example 7

[0060] The raw materials used in this comparative example to prepare the negative electrode active material are the same as those in Example 1. The above raw materials are used, and the method for preparing the negative electrode active material and the pole piece provided in Example 1 is referred to, to prepare the negative electrode active material and the pole piece of this comparative example. The difference from Example 1 is that the pore diameter of the amorphous carbon material used in this comparative example when preparing the negative electrode active material is 40nm. In addition to the above differences, the raw materials and process steps used in this comparative example are strictly consistent with those in Example 1.

[0061] Test Case

[0062] 1. Test subjects and control subjects

[0063] The antimony-carbon composite materials prepared in Examples 1 to 8 and Comparative Examples 1 to 7 were used as test objects in this test example; and metal antimony was used as the negative electrode active material, marked as a control object.

[0064] 2. Assembly of secondary batteries

[0065] The pole pieces prepared in different embodiments and comparative examples are used as negative pole pieces, lithium pieces are used as positive pole pieces, and Celgard 2500 is used as a diaphragm, wherein the diaphragm is a disc with a diameter of 16 mm, and the pole pieces are all discs with a diameter of 12 mm. The electrolyte is prepared using ethylene carbonate, diethyl carbonate, fluoroethylene carbonate, and lithium hexafluorophosphate. First, ethylene carbonate and diethyl carbonate are mixed in a volume ratio of 1:1, and then fluoroethylene carbonate and lithium hexafluorophosphate are added to the mixed organic solvent obtained to obtain an electrolyte. The electrolyte finally obtained contains 1M lithium hexafluorophosphate and 5% volume ratio of fluoroethylene carbonate. Finally, in a glove box in an argon environment, the above-mentioned positive pole piece, negative pole piece, diaphragm, and electrolyte are assembled to obtain a button cell of model CR2032, and then the button cell is left to stand for 12h to 24h and the electrochemical performance is tested at a discharge current density of 100mA / g.

[0066] 3. Test items

[0067] (1) Compacted density of negative electrode active material layer: PRCD3100 (IEST-Yuan Neng Technology) was used to test the conductivity and compacted density of the test object, and the four-probe mode was selected for measurement.

[0068] (2) Ultimate compaction density of negative electrode sheet: The negative electrode sheet is compacted and tested, and the experimental data with the maximum compaction without breaking is the ultimate compaction density.

[0069] (3) Antimony content of antimony-carbon composite material: Antimony content was determined according to the chemical analysis method for antimony ore GBT 15925-2010.

[0070] (4) Particle size distribution of negative electrode active material: The particle size of the antimony-carbon composite material was tested according to GB / T 19077_1-2003 particle size analysis-laser diffraction method.

[0071] (5) Cycle performance of secondary batteries: The test objects are tested according to GB / T 31485-2015, which covers the cycle life test methods, environmental conditions, test equipment and test result evaluation of battery packs.

[0072] (6) Energy density of secondary batteries: Battery weight energy density = battery capacity × discharge platform / battery weight, the basic unit is Wh / kg (watt-hour / kilogram). The battery capacity test is carried out in accordance with GB / T31484-2015 Cycle life requirements and test methods for power batteries for electric vehicles.

[0073] (7) X-ray diffraction spectrum detection: According to T / CSTM 00166.2-2020 Graphene Material Characterization Part 2 X-ray Diffraction Method, the negative electrode active material is tested by X-ray diffraction spectrum, and the peak intensity C of the characteristic peak of the (110) surface is read. 110 The peak intensity C of the characteristic peak of (002) surface 002 .

[0074] (8) Raman spectroscopy: Raman spectroscopy was performed on the antimony-containing negative electrode active material in accordance with the performance test method of laser confocal micro-Raman spectrometer GB / T 33252-2016, and the peak value at 1300 cm was read in the measured Raman spectrum. -1 The peak intensity of D near the position I D , the reading peak is at 1600cm -1 The peak intensity of G peak at nearby position I G .

[0075] 4. Test results and analysis

[0076] The test results of this test example are shown in Table 1. It can be seen from Examples 1 to 8 and Comparative Examples 1 to 3 that the energy density of the negative electrode active material prepared from the pure antimony-carbon composite material is lower than that of the negative electrode active material prepared from the antimony-carbon composite material and the amorphous carbon material. Figure 1 It can be confirmed that the three-dimensional network structure formed by the antimony-carbon composite material with a special antimony metal content and the amorphous carbon material with a mesoporous structure with a specific void diameter has a synergistic effect and can improve the rate performance of lithium-ion batteries.

[0077] In Example 1 and Comparative Examples 1 to 3, it can be confirmed that: on the one hand, the antimony-carbon composite material can enhance the structural stability of the negative electrode active material layer, solve the volume expansion problem caused by the storage of lithium ions or sodium ions in the negative electrode plate and the reaction between antimony metal and the electrolyte; on the other hand, the amorphous carbon material with a mesoporous structure can provide space for the negative electrode active material layer to store lithium ions or sodium ions, thereby enhancing the energy density of the negative electrode active material layer. Therefore, the antimony-carbon composite material can have good cycle performance, rate performance and high energy density by matching the amorphous carbon material.

[0078] In addition, by comparing the test data of Example 1, Comparative Example 4 and Comparative Examples 6-7, it can be found that the pore diameter of the mesoporous material will affect the storage of lithium ions or sodium ions in the negative electrode active material, thereby affecting the rate performance and energy density of the secondary battery.

[0079] In Examples 1 to 3, it can be found that by changing the mass ratio of the antimony-carbon composite material to the amorphous carbon material in the negative electrode active material, the cycle performance, rate performance, and energy density of the secondary battery using the negative electrode active material are affected. Among them, as the content of the antimony-carbon composite material increases, the cycle performance of the secondary battery shows a trend of first increasing and then decreasing.

[0080] In Examples 1 to 5, it can be found that when the antimony-carbon composite material has both I D / I G =0.5~1.6 Raman spectrum characteristics, and also has C 110 / C 002 = 0.043 ~ 0.085, in the antimony-carbon composite material, the carbon coating layer can provide reliable protection for the metal antimony core, so that it has good structural stability, and enhance the structural stability of the negative electrode active material layer, thereby improving its compaction density and ultimate compaction density.

[0081] In Examples 1 and 6-7, it can be found that when the particle size distribution of the antimony-carbon composite material satisfies D 50 =2.5~5μm, the particle size distribution of amorphous carbon materials meets D 50=0.55-0.65 μm, since the antimony-carbon composite material and the amorphous carbon material are evenly distributed, the negative electrode active material layer formed has a higher compaction density and ultimate compaction density.

[0082] Combined with the test data of Example 1, Example 8 and Comparative Example 2, the carbon coating layer in the antimony-carbon composite material has the effect of inhibiting the expansion of metallic antimony. Therefore, the structure of the antimony-carbon composite material including a metallic antimony core and a carbon coating layer improves the cycle performance, rate performance and energy density of the secondary battery.

[0083] In summary, the negative electrode active material provided by the present invention is based on the three-dimensional network structure formed in situ by the antimony-carbon composite material and the amorphous carbon material. On the one hand, it can improve the strength of the electrode material and ensure the structural stability of the negative electrode; on the other hand, the formed three-dimensional network structure can also provide expansion space for storing lithium ions or sodium ions, thereby improving the lithium storage performance of the negative electrode material. Therefore, the negative electrode active material provided by the present invention has good cycle performance, rate performance, high capacity and energy density, and can also meet the high endurance requirements of current commercial applications.

[0084] Table 1. Experimental results of test cases

[0085]

[0086] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A secondary battery, characterized in that: The secondary battery comprises a positive electrode sheet and a negative electrode sheet, wherein a negative electrode active material layer is provided on the negative electrode sheet, wherein the negative electrode active material layer contains an antimony-carbon composite material and an amorphous carbon material, and wherein, in the negative electrode active material layer, the antimony-carbon composite material: the amorphous carbon material = 8 to 10:1 according to the mass ratio; The amorphous carbon material is a mesoporous material, and the pore diameter of the amorphous carbon material is 20 to 30 nm; In the antimony-carbon composite material, the antimony element content is 1% to 50% by mass percentage; The particle size distribution of the antimony-carbon composite material satisfies D 50 =2.5-5 μm, the particle size distribution of the amorphous carbon material satisfies D 50 =0.55~0.65μm.

2. The secondary battery according to claim 1, characterized in that: The specific surface area of ​​the amorphous carbon material is 700 to 900 g / m 2 .

3. The secondary battery according to claim 1, characterized in that: The oil absorption value of the amorphous carbon material is 30 to 600 mL / 100 g.

4. The secondary battery according to claim 1, characterized in that: The antimony-carbon composite material comprises a metal antimony core and a carbon coating layer.

5. The secondary battery according to claim 4, characterized in that: The antimony-carbon composite material satisfies: in the Raman spectrum of the antimony-carbon composite material, the peak intensity of the D peak is D The peak intensity of the G peak is G Ratio I D / I G =0.5~1.6; In the X-ray diffraction spectrum of the antimony-carbon composite material, the peak intensity C of the characteristic peak of the (110) surface 110 The peak intensity C of the characteristic peak of (002) surface 002 Ratio C 110 / C 002 =0.043~0.

085.

6. The secondary battery according to claim 1, characterized in that: The compaction density of the negative electrode active material layer is 1.5 to 1.7 g / m 2 .

7. The secondary battery according to claim 6, characterized in that: The thickness of the negative electrode plate is 70-90 μm.

8. The secondary battery according to any one of claims 1 to 7, characterized in that: A positive electrode active material layer is provided on the positive electrode plate, and the positive electrode active material contained in the positive electrode active material layer includes at least one of nickel-cobalt-manganese ternary material, lithium iron phosphate material, lithium iron manganese phosphate material, lithium cobalt oxide material, and lithium-rich manganese-based material.

9. A drone, characterized in that: The drone comprises a battery system, and the battery system comprises the secondary battery according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Negative electrode for rechargeable lithium battery and rechargeable lithium battery including same

    CN103811732A

  • Graphene-carbon-SiO2 lithium ion battery anode material with shell-shell-core structure

    CN111732093A

  • Antimony-based composite negative electrode material and preparation method and application thereof

    CN115377378A

  • Negative plate and sodium ion battery

    CN116825951A

  • Antimony-containing negative electrode active material, preparation method thereof and lithium ion battery

    CN117239078A